The influence of cadmium contamination and salinity on the survival, growth and phytoremediation capacity of the saltmarsh plant Salicornia ramosissima - Pedro, Carmen A. (2013)
The major aim of this study was to evaluate the capacity of Salicornia ramosissima on Cadmium phytoremediation under distinct salinities and, consequently, the toxic effects on the plant's development. A greenhouse experiment was performed, using two Cd concentrations (50 and 100 μg l−1) in different salinities (0, 5 and 10). Mortality and weight variation, observed at the end of the experiment, showed significant differences between some treatments, meaning that these variables were affected by the salinity and Cd concentrations. The highest Cd accumulation was detected in the roots, and decreased with the increase of salinity and Cd concentration. S. ramosissima is a potential candidate for Cd phytoremediation at salinities close to 0 and its capabilities in Cd phytoaccumulation and phytoestabilization proved to be quite interesting. The optimization of phytoremediation processes by S. ramosissima could turn possible the use of this plant in the recovery of contaminated ecosystems.